Akmeological Vocational Orientation Of The Individual - Ernazarova Gulnora Oblakulovna (Zien Journals, 2022)
In this article, the pedagogical theoretical and practical basis for the introduction of an acmeological approach to the system of continuous education, its relevance, the specific content of acmeological orientation is to plan future specialists to carry out their professional activities, the development of skills-oriented in the context of specific components of the acmeological orientation of the individualtirishga the importance
Keywords: system of continuous education; akmeological approach; akmeological orientation; future specialists